An Investigation of The Role of Information in Decision Making To Enhance Performance: A Case of The Housing Real Estate Sector in Nairobi, Kenya - Karanja, Juliet (Daystar University, School of Business and Economics, 2013)
The demand for new housing units in urban areas currently stands at 150,000 units annually yet statistics show only 23% of this demand is being met. In order to ensure sustainable development of enterprises, stakeholders must pay attention to the needs of customers in the real estate sector while maintaining quality and realistic prices. The aim of the study was to examine the role of information in correlation with all stakeholders involved and how that information was useful towards decision making and performance enhancement. The study examined the theoretical framework that the real estate sector operates under, the need for housing as the major driving force in the real estate sector, services offered by selected professionals in the sector and most importantly overall performance and challenges faced in the sector. The study adopted exploratory design which involved collection of primary data from selected stakeholders in the real estate sector who were, conveyance advocates, architects, project managers and developers and bankers. The study established that having the right information and using that information to make decisions that enhanced performance of the industry for example the financial and social economic perspective. This is in relation to managing fluctuating exchange and interest rates, bureaucratic processes for council approvals, complex statutory requirements. Formulation of proper strategies would respectively lead to enhanced information technology, high returns derived through demand as well as innovative products and services and accessible mortgage and construction financing. The study recommended that effort should be made by the government together with the private sector in developing centralized approval systems to encourage investment in the sector. Global demographics on trends in the industry should be adopted for benchmarking purposes as well as technological advancement needed to develop the industry.
MASTER OF BUSINESS ADMINSTRATION in Strategic Management
Keywords: new housing units; real estate sector; decision making and performance enhancement; financial and social economic perspective